Prontidão das unidades de saúde da atenção primária para avaliação antropométrica em Campo Grande-MS - Wagner, Marielly (2022)
Monitoring the nutritional situation is an essential management tool, supporting the planning, execution and evaluation of health actions. Therefore, the objective of this study was to assess the readiness of Primary Care Health Units for anthropometric assessment in Campo Grande, MS. An adapted questionnaire was applied to the technical references of each health unit related to Primary Health Care in the municipality in the year 2021 on the functioning, infrastructure, material and human resources, in addition to actions carried out related to Food and Nutrition Surveillance (VAN) . The results show a heterogeneous situation of the units in the municipality according to the Readiness Index for VAN, saying that there are units that are more prepared (40.3%) and also unprepared (41.8%) for VAN within the same territory. For this, some improvements are needed, such as equipment, training of health professionals from the collection of anthropometric data and inclusion in the system, as well as food consumption markers, in addition to raising awareness of the importance of analyzing the reports generated, as well as by the municipal managers, aiming at valuing SISVAN as an essential health information system for the organization and management of care for the food and nutritional situation in Campo Grande.